(Considerations upon human nature in Aristotle’s thought) - Benéitez Prudencio, José Javier (Revista de Filosofía, 2012)
Aristotle says that only humans can speak and the speech capability is a proper criterion of humanity. Speech is also designated by Aristotle to indicate the right and the wrong. He finishes by saying that it is partnership in these things that makes a city. Ultimately a human being who is not in a polis, would not really be a human being at all? Would this human being then be no more human than a statue with a human form?